CBCT Evaluation of Root Canal Morphology of Maxillary First Premolar in Saudi Subpopulation - Pullishery Fawaz; Alhazmi Khalid A; Nazer Mohammed I; Alkhamis Ahmed; Meer Fernas M. S; Halteet Firas A; Sendiyoni Assil M. I; Taher Abdulkader O. H (Wolters Kluwer Medknow Publications, 2024)
Background and ObjectiveClinicians must possess a comprehensive understanding of variations in canal morphology and configuration during endodontic procedures to enhance treatment success. This study aims to assess and analyze the canal configurations of maxillary first premolars using Cone-Beam Computed Tomography within the sub-population of Western Saudi Arabia. Materials and MethodsIn this cross-sectional study, following the acquisition of ethical clearance from Batterjee Medical College in Jeddah, Saudi Arabia, a retrospective examination of Cone-Beam Computed Tomography (CBCT) scans of maxillary first premolars in adult patients was conducted. The study focused on quantifying the number of canals and characterizing their configurations, with classification based on Vertucci's categorization. ResultsThe study examined 399 CBCT images of maxillary first premolars, revealing that type IV canal configurations were the predominant morphology (56.9%), followed by type V (24.6%). Significant gender-related disparities were observed, with females displaying a higher incidence of types I and V canals. At the same time, males exhibited a greater prevalence of types IV and VI canals. Notably, no substantial associations were discerned between canal types and age groups. ConclusionWithin the context of maxillary first premolars, type IV canal configuration emerged as the most prevalent. Gender-based distinctions were evident, with females predominantly presenting types I and V canal configurations, whereas males displayed a higher occurrence of types IV and VI canal configurations.